On data and trends in horizontal inequality - Carla Canelas (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2022)
Economic, social, and political inequalities are at the forefront of today's public debate. While governments around the world have made conscious efforts to promote social inclusion, and major progress in fulfilling basic needs has been witnessed during the last decades, certain groups of people are still left behind in many domains of life. This paper aims to summarize recent horizontal inequality trends across and within countries and to better understand these changes over time. Overall, horizontal inequalities have been falling in the developing world, in spite of significant country variation. Importantly, significant differences exist for different inequality dimensions, i.e. economic, social, political. In terms of data, few cross-country horizontal inequality datasets are available for research. In general, there is a trade-off between the coverage of countries and time periods as well as comparability of the results between countries and years. Contrary to vertical inequalities, there has not been a systematic effort to construct and maintain an up-to-date dataset on horizontal inequalities.
Keywords: C80; D63; I24; J15; 330; inequality; group-based inequality; horizontal inequality; ethnic groups